Evaluation of General Practice Computer Templates - See Tai, S.; Nazareth, I.; Donegan, C.; Haines, A. (Methods of Information in Medicine, 1999)
We conducted a pilot randomised trial of computerised templates for the management of asthma and diabetes in general practice in six general practices in North London. Uptake of the guidelines by general practitioners and practice nurses was assessed using qualitative (semi-structured interviews designed to assess the users’ views) and quantitative (change in use of the template during the study period) outcome measures. The practice nurses used the templates frequently but general practitioners rarely used them. Several reasons were offered for non-use of the templates, such as the length of the template and non-involvement in the care of asthma or diabetes. Despite this, however, health professionals were favourably disposed to the use of templates for general clinical care. Pilot investigations of computerised templates are best achieved by observational or quasi-experimental methods rather than a randomised controlled trial. The use of both qualitative and quantitative methods in this study allowed exploration of the barriers to use of computers.
Keywords: General Practice; Computers; Decision-support Systems; Templates; Randomised Studies